1. Y=X-4
2. Y=X*4
3. Y=X+3
4. Y=X/6
<span>Y is directly proportional to x^2. It could be represented by the expression:
y </span>α x^2
We can make it into an equality by inserting the proportionality constant, k.
y = kx^2
k would be constant for any value of y with a corresponding value of x. We solve the problem by this concept as follows:
y1/(x1)^2 = y2/(x2)^2
10/(x1)^2 = y2/(x1/2)^2
10/4 = y2
Therefore, when the value of x is halved, y is equal to 10/4.
Answer:
Step-by-step explanation:
Given A = 5i + 11j – 2k and B = 4i + 7k, the vector projection of B unto a is expressed as
b.a = (5i + 11j – 2k)*( 4i + 0j + 7k)
note that i.i = j.j = k.k =1
b.a = 5(4)+11(0)-2(7)
b.a = 20-14
b.a = 6
||a|| = √5²+11²+(-2)²
||a|| = √25+121+4
||a|| = √130
square both sides
||a||² = (√130)
||a||² = 130
<em>Hence the projection of b unto a is expressed as </em><em></em>
The simplification of the expression is 28. The mistake in your calculation occurred in step 3.
<h3>What is the process involved in simplifying expression involving brackets?</h3>
TO simplify expressions involving brackets, we use a common method called BODMAS (Brackets, Of, Division, Multiplication, Addition, and Subtraction).
This means that we will first solve the expression in brackets first, followed by division, multiplication, addition, and subtraction as the case may be.
Now, from the given information, we have:
= 22+6[(14-5)÷3(17-14)]
solving parameters in the bracket first, we have:
= 22 + 6[(9) ÷3(3)]
= 22 + 6[(9) ÷9]
- The above step is where you missed it from your calculation, you must first open all brackets within brackets before solving them.
= 22 + 6[(9) ÷9]
= 22 + 6[ 1]
= 22 + 6
= 28
Learn more about simplifying expressions here:
brainly.com/question/723406
#SPJ1